An Essay on Adaptive Development - Filartiga, Gabriel Braga (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2019)
Development theory and practice need a new approach that, more than pointing out institutions to be improved, unveils the underlying mechanisms of path dependent processes of underdevelopment. This paper presents insights for such approach while making the statement that development is not exclusively an issue of interventionism, but rather must be taken from the perspective of spontaneous order. The starting point is the idea that development is an evolutionary process of trials, errors, learning and adaptation. The keystone is the concept of learning as a process of adaptive reorganization that links the microgenesis of capabilities and institutions to the production of social goods. The main argument in that adaptive efficiency is the product of an evolutionary process in which certain types of learning prevail, locking societies in vicious cycles of underdevelopment or unlocking the path to prosperity. When individuals and groups learn reflectively, in the sense that they reflect upon not only their problem-solving tasks but also upon the assumptions underlying their actions, they are more likely to adaptively reorganize capabilities and institutions locally. Without such reflection, they keep locked in unreflective patterns of underdevelopment.